2022
DOI: 10.1136/jitc-2021-003497
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant programmed cell death 1 blockade combined with chemotherapy for resectable esophageal squamous cell carcinoma

Abstract: BackgroundProgrammed cell death 1 (PD-1) blockade induces tumor regression in patients with advanced esophageal squamous cell carcinoma (ESCC); however, little is known about the efficacy of PD-1 blockade as neoadjuvant therapy in resectable ESCC. We aim to assess the safety and feasibility of using the combination of neoadjuvant PD-1 blockade with chemotherapy in patients with ESCC.MethodsPatients with previously untreated, resectable (stage II or III) ESCC were enrolled. Each patient received two 21-day cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
128
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(144 citation statements)
references
References 36 publications
13
128
3
Order By: Relevance
“…Yang W et al. ( 29 ) used a neoadjuvant regimen consisting of camrelizumab, nab-paclitaxel, and carboplatin for esophageal cancer, and the final pCR rate was 25% (5/23). Yang P et al.…”
Section: Discussionmentioning
confidence: 99%
“…Yang W et al. ( 29 ) used a neoadjuvant regimen consisting of camrelizumab, nab-paclitaxel, and carboplatin for esophageal cancer, and the final pCR rate was 25% (5/23). Yang P et al.…”
Section: Discussionmentioning
confidence: 99%
“…All of the above aspects may be closely related to the sustained survival benefit of this patient after receiving treatment. It has been reported that priming of CD4+ and CD8+ T cells contributes to signaling to cytotoxic T lymphocytes and further establishes effective and durable antitumor immunity ( 31 ), unfortunately, in this patient, changes of tumor-infiltrating CD4+ and CD8+ lymphocytes were not monitored during treatment, and it is not clear whether the patient’s durable immune response is related to the increase in CD4+ and CD8+ after treatment.…”
Section: Discussionmentioning
confidence: 86%
“…Of the 21 studies included, there were 20 single-arm open-label cohort studies ( 15 , 19 37 ) and there was one two-arm open-label randomized controlled trial (RCT) ( 38 ). Of the 21 studies included, three are still ongoing ( 26 , 29 , 30 ) and 18 ( 15 , 19 25 , 27 , 28 , 31 38 ) have been completed. The main neoadjuvant immunotherapy drugs include pembrolizumab, sintilimab, and camrelizumab, amongst others.…”
Section: Resultsmentioning
confidence: 99%